Physicochemical and organoleptic analysis of pumpkin ice cream with the addition of porang flour as a stabilizer - Rohani, Sofia; Amaro, Moegiratul; Rahayu, Tri Isti (Jurnal Agrotek Ummat, 2025)
Porang belongs to the Araceae family, which is a type of tuber plant classified under the genus Amorphophallus. Porang contains a high level of glucomannan, ranging from 5–60%. Glucomannan has various benefits, one of which is as a stabilizer in ice cream production, potentially improving the texture, viscosity, and stability of the product. Meanwhile, the protein in porang tuber flour is 9.20%, starch 76.5%, fiber 25%, fat 0.20%. This study aimed to determine the physicochemical and organoleptic properties of pumpkin (Cucurbita moschata) ice cream with the addition of porang flour as a stabilizer. The experiment consisted of five treatments: K1 (0%), K2 (0.2%), K3 (0.4%), K4 (0.6%), and K5 (0.8%) porang flour, arranged in a Completely Randomized Design (CRD) with four replications, resulting in 20 experimental samples. The observed parameters included protein content, fat content, viscosity, melting time, overrun, emulsion stability, and organoleptic properties. Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level with SPSS software. If significant differences were found, further testing was conducted using the Honest Significant Difference (HSD) test at 5% for physicochemical parameters. For organoleptic data showing significant differences, the Kruskal-Wallis nonparametric test was applied. The results showed that the addition of porang flour affected the physicochemical and organoleptic quality of pumpkin ice cream. The best treatment was obtained with the addition of 0.4% porang flour (K3), which produced ice cream with protein content of 5.57%, fat content of 6.74%, overrun of 30.06%, melting time of 56.64 minutes, viscosity of 49,130.00 mPa·s, and emulsion stability of 90.89%. The product also had a soft texture, yellow color, and flavor and aroma that were preferred by the panelists.